2020
DOI: 10.48550/arxiv.2007.03849
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global solutions to the compressible Euler equations with heat transport by convection around Dyson's isothermal affine solutions

Calum Rickard

Abstract: Global solutions to the compressible Euler equations with heat transport by convection in the whole space are shown to exist through perturbations of Dyson's isothermal affine solutions [8]. This setting presents new difficulties because of the vacuum at infinity behavior of the density. In particular, the perturbation of isothermal motion introduces a Gaussian function into our stability analysis and a novel finite propagation result is proven to handle potentially unbounded terms arising from the presence of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Serre [22] and Grassin [7] proved global existence in the whole space for a special class of initial data by perturbing solutions to the vectorial Burgers equation. Recently, Rickard [20] proved globalin-time well-posedness of the Euler equations with heat transport by the pertubation of Dyson's [6] isothermal affine solutions, see below for details on affine solutions. In the other direction, Sideris [24] showed that singularities must form if the density is a strictly positive constant outside of a bounded set.…”
Section: Introductionmentioning
confidence: 99%
“…Serre [22] and Grassin [7] proved global existence in the whole space for a special class of initial data by perturbing solutions to the vectorial Burgers equation. Recently, Rickard [20] proved globalin-time well-posedness of the Euler equations with heat transport by the pertubation of Dyson's [6] isothermal affine solutions, see below for details on affine solutions. In the other direction, Sideris [24] showed that singularities must form if the density is a strictly positive constant outside of a bounded set.…”
Section: Introductionmentioning
confidence: 99%